2008
DOI: 10.1248/cpb.56.1466
|View full text |Cite
|
Sign up to set email alerts
|

.ALPHA.-Glucosidase Inhibitors from Garcinia brevipedicellata (Clusiaceae)

Abstract: In our continuous search for a a-glucosidase inhibitors from plants, four new depsidones named brevipsidones A-D (1-4) were isolated from stem bark of Garcinia brevipedicellata together with known damnacanthal, scopoletin and a mixture of stigmasterol and b b-sitosterol. Structural elucidations were made by spectroscopic analyses including 2D-NMR data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…α-Glucosidase inhibitors demonstrated a large clinical importance in the treatment of type II diabetes, and this therapeutic class is mainly sustained by acarbose, miglitol, and voglibose, the 3 of them being derived from natural products [5][6][7]. Despite the close structural homologies between these clinically-approved inhibitors (carbasugars and iminosugars), polyphenolics pertaining to typical lichen metabolite series were repeatedly reported to exert promising α-glucosidase inhibitory activities: depsides [8], depsidones [9,10], diphenylethers [11], fungal xanthones [11], terphenylquinones, and pulvinic acid derivatives [12].…”
Section: Introductionmentioning
confidence: 99%
“…α-Glucosidase inhibitors demonstrated a large clinical importance in the treatment of type II diabetes, and this therapeutic class is mainly sustained by acarbose, miglitol, and voglibose, the 3 of them being derived from natural products [5][6][7]. Despite the close structural homologies between these clinically-approved inhibitors (carbasugars and iminosugars), polyphenolics pertaining to typical lichen metabolite series were repeatedly reported to exert promising α-glucosidase inhibitory activities: depsides [8], depsidones [9,10], diphenylethers [11], fungal xanthones [11], terphenylquinones, and pulvinic acid derivatives [12].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of HMBC correlations cannot help to differentiate the two chemical shifts. However, further analysis of NMR data for existing structures revealed that the 13 C chemical shift of C‐5a is always higher than that of C‐9a. This observation is crucial in determining the structure of the depsidone B ring.…”
Section: Resultsmentioning
confidence: 98%
“…Some plants of Garcinia species have been studied scientifically and are known to have activity as an antidiabetic, among others Garcinia brevipedicellata [5], Garcinia mangostana [6], Garcinia nobilis [7], and Garcinia hanburyi [8]. The bioactive compounds that play a role in the α-glucosidase inhibitor from each of these plants that brevipsidones D, prenylated xanthones, xanthones, and polyprenylated xanthones [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds that play a role in the α-glucosidase inhibitor from each of these plants that brevipsidones D, prenylated xanthones, xanthones, and polyprenylated xanthones [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%